2007
DOI: 10.1038/cr.2007.83
|View full text |Cite
|
Sign up to set email alerts
|

JMJD3 is a histone H3K27 demethylase

Abstract: Histone methylation is an important epigenetic phenomenon that participates in a diverse array of cellular processes and has been found to be associated with cancer. Recent identification of several histone demethylases has proved that histone methylation is a reversible process. Through a candidate approach, we have biochemically identified JMJD3 as an H3K27 demethylase. Transfection of JMJD3 into HeLa cells caused a specific reduction of trimethyl H3K27, but had no effect on di-and monomethyl H3K27, or histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
210
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(219 citation statements)
references
References 29 publications
7
210
2
Order By: Relevance
“…The GST-pull-down experiments demonstrated that GST-RB, but not GST alone, interacted with JMJD3 ( Figure 4c). The JmjC domain at the C-terminus has been identified as the only conserved catalytic domain of JMJD3, 36 as schematically illustrated in Figure 4d. Also, as mentioned above, the demethylase activity of JMJD3 was necessary for inducing cellular senescence (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GST-pull-down experiments demonstrated that GST-RB, but not GST alone, interacted with JMJD3 ( Figure 4c). The JmjC domain at the C-terminus has been identified as the only conserved catalytic domain of JMJD3, 36 as schematically illustrated in Figure 4d. Also, as mentioned above, the demethylase activity of JMJD3 was necessary for inducing cellular senescence (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…The substrate was incubated with the purified fusion protein of GST-JmjC domain of JMJD3 in demethylation buffer (20 mM TrisHCl pH 7.3, 150 mM NaCl, 50 μM (NH 4 )2Fe(SO 4 )2+6(H 2 O), 1 mM α-ketoglutarate and 2 mM ascorbic acid) for 4 h at 37°C. 36,41 Substrate was reacted in a total volume of 40 μl of reaction mixture. The reaction was stopped with SDS loading buffer, and western blotting analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation is added by histone methyltransferases and removed by demethylases. Up to now, more than 20 histone lysine demethylases have been identified that can remove methyl groups from histones in a sequence-and methylation state-specific manner [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The histone lysine demethylases can be divided into two groups with different catalytic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lysine methylation at H3K9 is usually associated with regions of transcriptionally silenced chromatin. Recent studies indicate that histone methylation can be removed by two distinct classes of histone demethylases, namely, flavin adenine dinucleotide (FAD)-dependent [3] and JMJC-containing protein families [4][5][6][7]. The reversible process of histone methylation and demethylation has been implicated in multiple biological processes including heterochromatin formation, X-inactivation, genomic imprinting and silencing of homeotic genes.…”
mentioning
confidence: 99%